1996
DOI: 10.3181/00379727-213-44043
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties and Dynamics of Natriuretic Peptide Receptors

Abstract: ince the discovery of atrial natriuretic factor (ANF or ANP) in 1981 by De Bold et al. (l), S more than 6500 articles on the subject have appeared in the literature. For an extensive review on ANP and its receptors, the reader is directed to Reference 2. In this short review, we will consider in a noninclusive manner the dynamics and functional properties of natriuretic peptide receptors. ANP is a 28-amino acid polypeptide hormone secreted mainly by the heart atria in response to atrial stretch that results fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The clearance receptor for natriuretic peptides (NPRC), a candidate gene for essential hypertension, plays a key role in the regulation of plasma levels and biological effects of natriuretic peptides [1].…”
Section: Introductionmentioning
confidence: 99%
“…The clearance receptor for natriuretic peptides (NPRC), a candidate gene for essential hypertension, plays a key role in the regulation of plasma levels and biological effects of natriuretic peptides [1].…”
Section: Introductionmentioning
confidence: 99%
“…NPR-C is widely expressed in a variety of tissues, including adipose tissue. Although it has been reported that this receptor induces a G-protein-linked cAMP activation [13] and, thus is involved in the cellular mechanisms of the antigrowth properties of NPs, it is generally accepted that NPR-C plays a major role in the local modulation of the physiological effects of NPs, by modulating the final ANP and BNP binding to NPR-A and by acting as the clearance receptor of NPs [14]. Both ANP and BNP are rapidly removed from the circulation by this receptor [15].…”
Section: Function Of Nps and Metabolic Alterationsmentioning
confidence: 99%
“…Cardiac natriuretic peptides, atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) are potent inhibitors of aldosterone secretion (Anderson et al 1986, Holmes et al 1993, being effective antagonists of angiotensin II. The effects of both ANP and BNP on aldosterone secretion are mediated by natriuretic peptide receptor type A (NPRA, codified by the Npr1 gene), a membrane guanylyl cyclase with cGMP being the main intracellular messenger (Maack et al 1996).…”
Section: Introductionmentioning
confidence: 99%